Meteorology demystified - Gibilisco, Stan (McGraw-Hill, 2006)
The purpose of this book is to demystify weather. But while the book begins with a promising use of physical equations, these serve only to pad the book with test questions that are not further applied in the text to demystify (i.e., explain in causal terms) why things happen in the atmosphere. In addtion, it Presents an introduction to meteorology, providing information on understanding the science of air and water pressure systems, exploring the formation of tornadoes, hurricanes, and winter storms, and considering the impact of human activity on climate. There is a great deal of talk about what to do in the event of a thunderstorm, a hurricane, a tornado, and so on, but this information is readily available from any disaster center and elsewhere on the web. I came away from this book more mystified than when I opened it. A tempestuous disappointment.